2022
DOI: 10.1038/s41388-022-02353-3
|View full text |Cite
|
Sign up to set email alerts
|

Noncoding RNA actions through IGFs and IGF binding proteins in cancer

Abstract: The insulin-like growth factors (IGFs) and their regulatory proteins—IGF receptors and binding proteins—are strongly implicated in cancer progression and modulate cell survival and proliferation, migration, angiogenesis and metastasis. By regulating the bioavailability of the type-1 IGF receptor (IGF1R) ligands, IGF-1 and IGF-2, the IGF binding proteins (IGFBP-1 to -6) play essential roles in cancer progression. IGFBPs also influence cell communications through pathways that are independent of IGF1R activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 110 publications
0
7
0
Order By: Relevance
“…Several studies have reported that high levels of blood IGFs are associated with an increased risk of breast cancer [54][55][56][57][58][59]. IGF-binding protein (IGFBP) is one of the key regulators of IGF signaling as it functions as a reservoir of serum IGFs [54][55][56][57]59,60]. Based on these studies, increased levels of circulating IGF-1 and IGFBP3 are considered risk factors for breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that high levels of blood IGFs are associated with an increased risk of breast cancer [54][55][56][57][58][59]. IGF-binding protein (IGFBP) is one of the key regulators of IGF signaling as it functions as a reservoir of serum IGFs [54][55][56][57]59,60]. Based on these studies, increased levels of circulating IGF-1 and IGFBP3 are considered risk factors for breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Binding of IGF to the IGF receptor activates PI3K/Akt and ERK signaling leading to cancer cell survival, proliferation, and migration [ 46 ]. Conversely, IGFBP suppresses IGF-related signaling pathways by interrupting the IGF-to-IGF receptor binding [ 47 , 48 ]. In our study, we found that ME treatment upregulated the expression of IGFBP3, the most abundant IGFBP, and downregulated the activation of the PI3K-mTOR signaling pathway ( Figs.…”
Section: Discussionmentioning
confidence: 99%
“…5 and 6 ). According to a study by Kerr et al ., microRNA-10a, levels of which are increased by β-sitosterol, acts through the IGF- and IGFBP-related pathways in cancer [ 48 ]. This suggests that β-sitosterol in ME may play a crucial role in modulating the IGFBP-PI3K pathway in pancreatic cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Noncoding RNAs, including microRNAs (miRs) and lncRNAs, have an impact on IGF/IGF1R pathway activity (reviewed in ( 180 )). MiRs are double-stranded short RNAs that are binding to the 3’-upstream region (UTR) of mRNAs to block their translation or to induce their degradation ( 181 ).…”
Section: Regulation Of Igfbp5 Expressionmentioning
confidence: 99%